Implementasi Markerless Augmented Reality Location Based dalam Pelaksanaan Sistem Keamanan Lingkungan (Siskamling) - Muhammad Algier Mahesa; Fais Al Huda; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Maintaining security and the environment is a shared responsibility as citizens. One of the most important parts in maintaining security and the environment is the participation of the community. In this case the form of community participation to protect the environment is manifested in the form of a security and environmental system, one of the community's efforts to maintain security and the surrounding environment is to carry out patrols or siskamling activities. Meanwhile, the rapid development of technology forces us to keep up with these technological developments, especially in the world of information and communication technology. Technology plays an important role in the modern era as it is today, one of the technologies currently developing is Augmented Reality (AR). AR is a technology that combines virtual objects both 2D and 3D into a real environment and then projects these virtual objects in real time. Utilization of AR is done by implementing it on a system with the aim of combining virtual objects with real objects. Based on an interview with the security chief in question, it was not easy for officers to coordinate with each other with the Handy Talky (HT) communication tool, the coordination between officers was quite complicated because other officers and the field coordinator could not visually blend in with only the HT. Given these problems, this research implements Augmented Reality Location Based using the Navigation Coordinate System which is a coordinate system mapped from GPS points which will then become the coordinate points on the smartphone screen camera display. By implementing this Location Based Augmented Reality in an application with the Android platform, the Security and Security Service officers can visually unite other officers on their smartphone screens. In this study, usability testing was also carried out using the System Usability Scale method, with an average result of 77.25 which can show Augmented Reality applications that are easy to use by Security and Security Officers.